The Interface: Peace Walls, Belfast, Northern Ireland - James O'Leary (Footprint)
In 2013, the Northern Ireland Executive outlined a goal to ‘create a ten year programme to reduce, and remove by 2023, all interface barriers’ in Northern Ireland.  This unexpected statement helped to focus attention on the difficulties inherent in making this commitment a reality.  Made during a period of fieldwork in Belfast between 2014 and 2016, this work of text and image frames the thirteen clusters of separation barriers that divide communities across Belfast as a single system entitled ‘The Interface’.